2007
DOI: 10.1089/end.2006.0379
|View full text |Cite
|
Sign up to set email alerts
|

Need for Ancillary Procedures among Patients Undergoing Tubeless Percutaneous Renal Surgery for Nephrolithiasis

Abstract: Patients who are eligible for tubeless PCNL are unlikely to need a secondary procedure, and residual stones can most often be treated with SWL. Patients who required nephrostomy tubes had more complicated disease and a greater need for subsequent surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, these findings were contradictory to those of the Bellman group, who found that 78% of their patients undergoing tubeless PCNL were stone free and only 17% required ancillary procedures, mostly SWL for residual fragments. 27 In our series, 90.27% of the patients in the study group and 86.11% of the patients in the control group were stone free after PCNL. Only five patients were subjected to postoperative SWL.…”
Section: Discussionmentioning
confidence: 51%
“…However, these findings were contradictory to those of the Bellman group, who found that 78% of their patients undergoing tubeless PCNL were stone free and only 17% required ancillary procedures, mostly SWL for residual fragments. 27 In our series, 90.27% of the patients in the study group and 86.11% of the patients in the control group were stone free after PCNL. Only five patients were subjected to postoperative SWL.…”
Section: Discussionmentioning
confidence: 51%
“…16 Kim and coworkers 16 found that only 31% of their patients were stone free, as determined by postoperative CT scan after the first procedure, but the success rate increased to 95.2% after secondary PCNL. However, these findings were contradicted by those of the Bellman group, 17 who found that 78% of their patients undergoing tubeless PCNL were stone free and only 17% required ancillary procedures, mostly SWL, for the residual fragments. In present series, we found that 93.1% of the patients in the control group and 91.3% of the patients in the experimental group were stone free after PCNL.…”
Section: Shah Et Al 196mentioning
confidence: 89%
“…Brusky et al. [15] reported a 13% incidence of re‐treatment in the tubeless group, for non‐staghorn calculi; 15% of the patients needed an auxiliary procedure. Most of the stones remaining are CIRF; it was confirmed that CIRF can lead to symptomatic episodes in the future and hasten stone recurrence.…”
Section: Discussionmentioning
confidence: 99%